Heritable morphological differentiation in salmonids from two distinct stream types. Issue 5 (3rd September 2019) - Dermond, Philip; Sperlich, Nicola; Brodersen, Jakob
Abstract: We tested for phenotype‐to‐habitat associations in brown trout Salmo trutta populations from two ecologically different habitat types; i.e ., groundwater and surface‐water‐fed streams. Additionally, we raised captive offspring from two such populations under standardised conditions to test whether potential phenotypic differentiation would be passed on to offspring. We found analogous differentiation by habitat in multiple wild populations. Some of these morphological differences were at least partially inherited by offspring. We suggest that this could have implications for both scientists and fisheries authorities studying or managing trout populations.